Criminalisation of Sex Work: A Critical Approach to Criminalisation Theories from a Human Rights Perspective - Başak Ekinci (Annales de la Faculté de Droit d’Istanbul)
Criminalisation is a popular legal approach to sex work. It adopts the view that sex work is harmful and wrong both for sex workers and the community. This argument seemingly coincides with fundamental principles of criminalisation, namely harm and wrong principles. However, I provide a new approach to criminalisation theories which introduces a real restriction on the state’s authority to criminalise. In doing so, I first discuss that harm and wrong principles are only defining principles which determine the scope of behaviours that can be considered within the criminal law realm. On the other hand, the restricting principles, namely those of proportionality and prohibition of discrimination, determine the boundaries of the state’s authority to criminalise the defined harmful wrongdoings. After I apply the defining principles to sex work, I investigate whether the restricting principles give countervailing reasons against criminalisation. The conclusion is that, unless it is proven to be contrary in a specific jurisdiction, sex work should not be criminalised because prima facie reasons cannot turn into all-things-considered reasons to justify criminalisation of sex work.